MULTI SCALE REPRESENTATION FOR REMOTELY SENSED IMAGES USING FAST ANISOTROPIC DIFFUSION FILTERING - Vanhamel, I; Alrefaya, Musa; Sahli, Hichem (IEEE International Symposium on Geoscience and Remote Sensing, 2010)
Object based image analysis has gained on the traditional perpixel multi-spectral based approaches. The main pitfall of using anisotropic diffusion for creating a multi scale representation of a remotely sensed image remains the computational burden. Producing the coarser scales in a multi scale representation or, diffusing spatially large images involves significant time and resources. This paper proposes a fast approach for anisotropic diffusion that overcomes spatial size limitations by distributing the diffusion as individual sub-processes over several overlapping sub-images. The overlap areas are synchronized at specific diffusion time ensuring that the fast approximation does not deviate too much from its single process equivalent. This demonstrated for an image, which can be diffused using a traditional sequential approach. In addition, experimental data for very large images that can not efficiently be processed using a sequential approach is illustrated.
Keywords: Image enhancement, anisotropic diffusion, (very) high resolution images, multi-process, parallel computing